NOX5-L can stimulate proliferation and apoptosis depending on its levels and cellular context, determining cancer cell susceptibility to cisplatin - Dho, So Hee (Oncotarget, 2015)
The NADPH oxidase, NOX5, is known to stimulate cell proliferation in some cancers by generating reactive oxygen species (ROS). We show here that the long form of NOX5 (NOX5-L) also promotes cell death, and thus determines the balance of proliferation and death, in skin, breast and lung cancer cells. Moderate expression of NOX5-L induced cell proliferation accompanied by AKT and ERK phosphorylation, whereas an increase in NOX5-L above a certain threshold promoted cancer cell death accompanied by caspase-3 activation. Notably, cisplatin treatment increased NOX5-L levels through CREB activation and enhanced NOX5-L activity through augmentation of Ca(2+) release and c-Abl expression, ultimately triggering ROS-mediated cancer cell death—a distinct pathway absent in normal cells. These results indicate that NOX5-L determines cellular responses in a concentration- and context-dependent manner.